Consequences of Using Artificial Intelligence in the Process of Studying at a Law School - Tatiana V. Efimtseva; Elena E. Zhukova (RUDN Journal of Law)
In education, student motivation is a crucial issue. This study focuses on the motivation of non-linguisticcs students to learn a foreign language. Practice has shown that a combination of factors, including effective organization of the learning process and the extensive use of modern technologies, enhances motication in education. The emergence of artificial intelligence (AI) and the widespread application of neural networks have both positive and negative consequences. Therefore, AI can be used for both the benefit and detriment of students. To ensure that new technologies serve progress, changes to the existing order are necessary. The study aims to examine the possibilities of using AI to train lawyers and teach English to law students. It identifies AI advantages and disadvantages and formulates recommendations to improve the educational process using neural networks. The research methodology is based on the dialectical method of scientific knowledge. This interdisciplinary study analyses the works of foreign and domestic experts on various topics, primarily concerning the application of AI in education.